Zygoma fracture caused by penetration of atypical object into the face (Research, Society and Development, 2022)
Fractures of the zygomatic bone, when displaced, usually have great clinical repercussions, whether functional or aesthetic. Many of the aesthetic complaints are due to the zygoma being located in a very prominent region on the face. The main functional limitations reported by patients are diplopia, limited mouth opening and paresthesia in the regions innervated by the infraorbital nerve. They are usually caused by physical aggression, traffic accidents or by the victim of a firearm projectile, but very rarely being caused accidentally in the author of the shot. This work aims to report the immediate handling of a rare accident caused by the penetration of a firearm component in the face of the shooter, in which the initial conduct was to remove the object, preserving as much tissue as possible. soft and hard, and a second surgical time for bone fixation after adequate planning, showing the importance of directing the planning according to the patient's complaints. In this way, the professional must have a good knowledge of the main signs and symptoms of facial fractures, in order to provide an adequate diagnosis and surgical planning to the patient, especially in cases of more atypical traumas.